LIFTING AS WE CLIMB: EXPERIENCES OF BLACK DIVERSITY OFFICERS AT THREE PREDOMINANTLY WHITE INSTITUTIONS IN KENTUCKY - Johnson, Erica NićCole (2010)
Recently, colleges and universities across the country have created executive level positions responsible for institutional diversity. The origins of this work within higher education lay in the civil rights movements and its consequences for desegregation of higher education. Early diversity officer positions usually resided within student affairs. However, as the responsibilities of these offices have changed, the reporting lines have also changed such that diversity officers are now commonly situated within academic affairs. This exploratory study examines these administrative positions responsible for diversity at southern white institutions. The research takes an in-depth look at how these positions have shifted over time and how people who hold these positions understand their work. This study presents an analysis of nine personal narratives of diversity officers at three predominantly white institutions in Kentucky from the early 1970s to the present. Counterstories, or stories that challenge majority accounts, are used to elicit the experiences of the black diversity officers. The analysis uses critical race theory to begin telling stories that have been muted. Pigeonholing and its relevance to the counterstories of the administrators are discussed to contextualize the administrators’ experiences at predominantly white institutions. The shift in responsibilities and reporting lines and changes in required credentials resulted in tensions, including intraracial tensions, among the diversity officers. Despite the tensions between generations of officers, these administrators shared a common interest in racial uplift. This was evident as they discussed what attracted them to positions responsible for diversity. In the past, scholars writing on black diversity officers suggested that the positions were the result of tokenism; however, administrators holding these positions view themselves and their roles as an opportunity to help others on their educational journeys